2014
DOI: 10.4067/s0718-221x2014005000013
|View full text |Cite
|
Sign up to set email alerts
|

Study on preparation and properties of phenol-formaldehyde-chinese fir liquefaction copolymer resin

Abstract: A new zero-waste and zero-pollution composite adhesive labeled Chinese fir-based adhesive for exterior plywood was synthesized by blending alkaline Chinese fir (Cunninghamia lanceolata) liquid with a small amount of phenol-formaldehyde (PF). The free phenol and free formaldehyde content of the Chinese fir-based adhesive were sharply decreased compared to normal PF resin by more than 50%. The synthetic adhesive show with excellent water resistance and environmental friendliness, which had a 28h boil-dry-boil we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…The values determined for this parameter were around 40% and presented a slight increase in the formulations where inorganic nanoparticles were added owing to the small increment of the solid content. The values of the NVC were lower compared to other works from the literature 52,53 and especially compared to the typical phenol formaldehyde resins. 54 The apparent viscosity was another parameter displaying a similar tendency to the density and the nonvolatile content.…”
Section: ■ Results and Discussioncontrasting
confidence: 75%
“…The values determined for this parameter were around 40% and presented a slight increase in the formulations where inorganic nanoparticles were added owing to the small increment of the solid content. The values of the NVC were lower compared to other works from the literature 52,53 and especially compared to the typical phenol formaldehyde resins. 54 The apparent viscosity was another parameter displaying a similar tendency to the density and the nonvolatile content.…”
Section: ■ Results and Discussioncontrasting
confidence: 75%
“…It was observed that in the increase of bio-oil, the curing temperature decreased from 95°C of pure PF to 60°C of 20% BOPF resin. As a result of the bio-oil addition of 20 or 10%, the curing temperature of BOPF resins was relatively near to that of PF resins (Lin et al 2014;Özbay et al 2020; Figure 3).…”
Section: Dsc Analysismentioning
confidence: 96%
“…Under these conditions, biomass liquefaction with polyhydric alcohols, such as glycerol, ethylene glycol, or polyethylene glycol (PEG) (Kurimoto and Tamura 1999;Yamada and Ono 2001;Niu et al 2011;Martins et al 2013) affords large molecules that can be subsequently polymerized to produce adhesives, plastics, or other polymers Zhang et al 2007;Lin et al 2014). The choice of biomass liquefying solvent, as well as the catalyst (e.g., acid, base or other cyclic carbonates), will influence the composition of molecules extracted (Xie and Chen 2005).…”
Section: Introductionmentioning
confidence: 99%